2017
DOI: 10.1002/ijch.201600097
|View full text |Cite
|
Sign up to set email alerts
|

Flexible N‐Termini of Amyloid β‐Protein Oligomers: A Link between Structure and Activity?

Abstract: Revised amyloid cascade hypothesis of Alzheimer′s disease (AD) states that amyloid β‐protein (Aβ) triggers the disease through formation of soluble low molecular weight (LMW) assemblies, called oligomers, which are challenging to characterize experimentally as well as computationally due to their heterogeneous and polymorphic nature, lack of ordered structure, and short lifetimes. Recent findings challenge the view of Aβ oligomers as exclusively toxic entities by revealing their dual, protective and disruptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 157 publications
(239 reference statements)
2
23
0
Order By: Relevance
“…To examine the effect of X-linking on free energy landscapes of Aβ oligomers, we calculated PMFs of X-linked and non-Xlinked Aβ 40 and Aβ 42 monomers, dimers, trimers, and hexamers using two reaction coordinates: the N-CM distance and the hydrophobic CG-SASA as described in the Methods section (Figure 15). The N-CM distance was selected because previous DMD4B-HYDRA studies of Aβ 40 and Aβ 42 oligomers revealed distinct alloform-specific NTR conformations 23 and the hydrophobic CG-SASA quantifies the ability of the conformation to shield hydrophobic amino acids from the solvent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To examine the effect of X-linking on free energy landscapes of Aβ oligomers, we calculated PMFs of X-linked and non-Xlinked Aβ 40 and Aβ 42 monomers, dimers, trimers, and hexamers using two reaction coordinates: the N-CM distance and the hydrophobic CG-SASA as described in the Methods section (Figure 15). The N-CM distance was selected because previous DMD4B-HYDRA studies of Aβ 40 and Aβ 42 oligomers revealed distinct alloform-specific NTR conformations 23 and the hydrophobic CG-SASA quantifies the ability of the conformation to shield hydrophobic amino acids from the solvent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…50 It has been thus proposed that Xlinked Aβ 40 and Aβ 42 oligomers may be the proximate neurotoxic species in AD. 23 DMD4B-HYDRA simulations of Aβ 40 and Aβ 42 oligomer formation have been shown to capture alloform-specific oligomer size distributions and distinct structural features of Aβ 40 and Aβ 42 oligomers. 25,30 Recently, the effect of simple Xlinking via tyrosines on Aβ 40 and Aβ 42 oligomer formation and structure was explored using the DMD4B-HYDRA approach.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to elucidate atomistic details of Aβ oligomer structure and identify the structural aspects that could mediate their activity, in both health and disease. Molecular dynamics (MD) provides atomistic structural information about Aβ oligomers, which complements experimental findings by offering mechanistic insights into the oligomer formation and structure that are not accessible to experimental studies. , Despite significant computational progress in the past two decades, time evolution of Aβ aggregation from initially monomeric peptides is still not easy to study by fully atomistic explicit-solvent MD.…”
Section: In Silico Aβ Oligomers Form Water-permeable Poresmentioning
confidence: 99%
“…Structural analysis of cross-linked Aβ oligomers reported by Zhang et al revealed increased solvent exposure at the Nterminal region relative to the respective non-cross-linked conformations, 70 which has been previously associated with increased oligomer toxicity. 50 Experimental results on stabilization of Aβ oligomers through CHICUP 34 and the follow-up computational studies exploring the cross-linking mechanism 68,70 provide important insights into the cross-linking process and elucidate the role of phenylalanine hydroxylation in cross-linking under oxidative stress conditions.…”
Section: ■ Insights Into Potential Cross-linking Mechanismsmentioning
confidence: 99%